The Theoretical Foundations of the Local Currency Initiative - Varga, József; Madaras, Attila (Acta Scientiarum Socialium, 2013)
The Theoretical Foundations of the Local Currency Initiatives As an introductory part of this paper we investigate the emergence of the idea of local currency and the circumstances of its introduction. As financial (macro-finance) experts we believe that in Hungary more and more exaggerated and overoptimistic expectations are coming up towards local currency. While not underestimating the series of enthusiastic and inspiring studies and presentations, our task as researchers is to logically think the economic consequences of community currencies over, to calmly summarize the results, and then to turn that eager activity into organizational work. In the spirit of this train of thought, we first clarify the definition of money, local currency and that of some basic concepts related to them. Following that, we investigate the financial benefits of the introduction of local currency. In the center of the study stands the interest income derived from money creation („seigniorage-effect”). Next we examine the other financial benefits of local currency and shortly discuss the non-financial advantages as well. Finally, after the theoretical explanations we summarize the quantification of local currency from the top (the domestic macro data) as well as from the bottom (analysis of some income data of the Subregion of Kaposvár).